Political Evolution at NATO Level in Post Cold War Era - Tomescu Cătălin Tomiţă (Scientific Bulletin, 2015)
The beginning of the post Cold era sounds like that: „The world has changed dramatically. The Alliance has made an essential contribution. The peoples of North America and the whole of Europe can now join in a community of shared values based on freedom, democracy, human rights and the rule of law. As an agent of change, a source of stability and the indispensable guarantor of its members' security, our Alliance will continue to play a key role in building a new, lasting order of peace in Europe: a Europe of cooperation and prosperity”[1].